(untitled) (The Journal of Medicine, Humanity and Media, 2024)
Medical crowdfunding plays an important role in promoting the development of medical public welfare. As there is not great enthusiasm for charity of the Chinese public, it is necessary to understand the relevant factors affecting the intention of medical crowdfunding. Based on the perspective of social capital, this study used WeChat Moments as a research scenario to explore the influence of tie strength and message framing on medical crowdfunding intention as well as the moderating effect of social capital through the method of experimentation. The results showed that the donation and sharing intention of participants in the scenario of strong relationship was significantly higher than that in the scenario of weak relationship. And structural and cognitive social capital had positive moderating effects on donation and sharing intention, respectively. When faced with loss-framed message, donation intention of participants was significantly higher than when they faced gain-framed message; When in the strong relationship scenario, participants were more willing to donate to projects that also used loss frame. This study provides practical guidance for fundraisers on how to better seek financial support and offers reference for promoting the development of "Internet+" medical public welfare.